“Red-Green” or “Brown-Green” Dichromats? The Accuracy of Dichromat Basic Color Terms Metacognition Supports Denomination Change - Moreira, Humberto; Lillo, Julio; Álvaro, Leticia (Frontiers in Psychology, 2021)
Two experiments compared “Red-Green” (R-G) dichromats’ empirical and metacognized capacities to discriminate Basic Color Categories (BCCs) and to use the corresponding Basic Color Terms (BCTs). A first experiment used a 102 related colors set for a pointing task to identify all the stimuli that could be named with each BCT by each R-G dichromat type (8 protanopes, 9 deuteranopes). In a second experiment, a group of R-G dichromats (15 protanopes, 16 deuteranopes) estimated their difficulty discriminating BCCs-BCTs in a verbal task. The strong coincidences between the results derived from the pointing and the verbal tasks indicated that R-G dichromats have very accurate metacognition about their capacities (they only had considerable difficulty discriminating 13 out of the total of 55 possible BCT pairs) and limitations (Brown-Green and Blue-Purple pairs were rated especially difficult to differentiate) in the use of BCTs. Multidimensional scaling (MDS) solutions derived from both tasks were very similar: BCTs in R-G dichromats were properly represented in 2D MDS solutions that clearly show one chromatic dimension and one achromatic dimension. Important concordances were found between protanopes and deuteranopes. None of these dichromats showed substantial difficulty discriminating the Red-Green pair. So, to name them “R-G” dichromats is misleading considering their empirical capacities and their metacognition. Further reasons to propose the use of the alternative denomination “Brown-Green” dichromats are also discussed. We found some relevant differences between the “Brown-Green” dichromats’ empirical and self-reported difficulties using BCTs. Their metacognition can be considered a “caricature” of their practical difficulties. This caricature omits some difficulties including their problems differentiating “white” and “black” from other BCTs, whilst they overestimate their limitations in differentiating the most difficult pairs (Brown-Green and Blue-Purple). Individual differences scaling (INDSCAL) analyses indicated that the metacognition regarding the use of BCTs in “Brown-Green” dichromats, especially deuteranopes, is driven slightly more by the chromatic dimension and driven slightly less by the achromatic dimension, than their practical use of BCTs. We discuss the relevance of our results in the framework of the debate between the Linguistic Relativity Hypothesis (LRH) and the Universal Evolution (UE) theories.